2007
DOI: 10.1007/s10811-007-9233-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light intensity and nitrogen starvation on growth, total fatty acids and arachidonic acid in the green microalga Parietochloris incisa

Abstract: The effects of light and nitrogen deficiency on biomass, fatty acid content and composition were studied in Parietochloris incisa, the unicellular freshwater chlorophyte accumulating very high amounts of arachidonic-acidrich triacylglycerols. P. incisa cultures grown on complete nutrient medium and under high light (400 μmol photons m − 2 s −1 ) showed the highest rate of growth in comparison to medium (200 μmol photons m −2 s −1 ) and low (35 μmol photons m −2 s −1 ) light intensity. Cultures grown under high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
141
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(159 citation statements)
references
References 26 publications
14
141
2
2
Order By: Relevance
“…They also found that the increase in PUFA and the decrease in MUFA were correlated with the increased neutral lipid content [33]. These results were similar to the study of Solovchenko et al [7] but opposite to the study of Lin et al [5]. Although the lipid containing a high content of PUFA may make the biodiesel susceptible to oxidation, it is easy to improve the saturation degree in certain chemical processes [1].…”
Section: Fatty Acid Composition Of Neutral Lipidsmentioning
confidence: 53%
See 2 more Smart Citations
“…They also found that the increase in PUFA and the decrease in MUFA were correlated with the increased neutral lipid content [33]. These results were similar to the study of Solovchenko et al [7] but opposite to the study of Lin et al [5]. Although the lipid containing a high content of PUFA may make the biodiesel susceptible to oxidation, it is easy to improve the saturation degree in certain chemical processes [1].…”
Section: Fatty Acid Composition Of Neutral Lipidsmentioning
confidence: 53%
“…Therefore, it may be helpful in the dissipation of excess light energy and prevention of the photochemical damage of algal cells [27]. Thus, more carbon flux generated from the photosynthesis is channeled to the lipid accumulation on a unit biomass basis when individual cell is exposed to a large quantity of light energy [7,28]. Therefore, the high and medium lights could promote the final biomass yield, lipid content, and yield, especially neutral lipid content.…”
Section: Effect Of Light Intensity On Total Lipids and Neutral Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…PUFAs are one of the most nutritionally important and essential fatty acids because they are key nutrients in animal nutrition, and the most algae are rich in these acids 43 . Nitrogen and phosphate are two important macronutrients for phospholipids because nitrogen and phosphorus starvation shifts the lipid metabolism from membrane lipid synthesis to neutral lipid storage 39,[44][45][46] . Results of the present study also showed clearly that peaks in PUFAs are related to nitrogen and phosphorus, but its correlation with potassium and magnesium was more evident.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of secondary pollution is solved due to very efficient biomass reuse and nutrient recycling. Moreover, the versatility of microalgae is further exploited in the production of biofertilizers, feed for animals and fine chemicals [10,11]. However, the macromolecular composition (lipids, carbohydrates, proteins, nucleic acids) and pigments contents of microalgae biomass are influenced by growth conditions.…”
Section: Introductionmentioning
confidence: 99%